Evolution, Interspecies Transmission, and Zoonotic Significance of Animal Coronaviruses - Parkhe, Prapti; Verma, Subhash (Frontiers in Veterinary Science, 2021)
Coronaviruses (CoVs) are single stranded RNA viruses that affect humans and wide variety of animal species including livestock, wild animals, birds and pets. These viruses have affinity for different tissues such as those of respiratory and gastrointestinal tract of most mammals and birds, and hepatic and nervous tissues of rodents and porcine. Since, CoVs target different host cell receptors and show divergence in the sequences and motifs of their structural and accessory proteins, they are classified into groups which may explain the evolutionary relationship between them. The interspecies transmission, zoonotic potential, ability to mutate at higher rate and emerge into variants of concern highlight their importance in the medical as well as veterinary field. The contribution of various factors that result in their evolution will provide better insight and may help to understand the complexity of coronaviruses in the face of pandemics. In this review, important aspects of coronaviruses infecting livestock, birds and pets, in particular their structure and genome organization having bearing on evolutionary and zoonotic outcomes have been discussed.